Atividade antinociceptiva e anti-inflamatória de Herissantia crispa (L.) Brizicky em camundongos - Pereira, Charlane Kelly Souto (2013)
The Herissantia crispa (L.) Brizicky (Malvaceae), is composed of substances that have proven activities, such as anti-inflammatory, antinociceptive and antioxidant. There are few reports in the literature of this plant, but previous studies have determined, that H.crispa characteristics of drugs with antinociceptive and sedative-hypnotic profile. The aim of this study was to evaluate the antinociceptive effect of H. crispa, using the ethyl acetate phase from H. crispa (FAEHc), hydroalcoholic phase (FHAHc) and two flavonoids isolated from this plant (tiliroside and lespedin), as well as the possible mechanisms involved in this activity and the anti-inflammatory effect. To determine the antinociceptive mechanisms of action and the anti-inflammatory activity only FAEHc was used. The experiments conducted in mice demonstrate that FAEHc, FHAHc and flavonóides, injected via i.p., promoted significantly antinociception in the formalin test, and also showed a significantly reduction in the glutamate-induced nociception. The antinociception produced by FAEHc was significantly reversed by pretreatment of animals with caffeine, atropine or L-arginine suggesting involvement of adenosinergic, muscarinic and oxidonitrergic systems, respectively. However, FAEHc antinociceptive response was not blocked when animals were pretreated with naloxone, yohimbine and glibenclamide, indicating that FAEHc probably is not acting through these pathways. The treatment of animals with FAEHc promoted significant reduction of the paw edema induced by carrageenan in the first 48 hours of the test. Furthermore, FAEHc significantly decreased leukocyte migration, particularly the influx of neutrophils, and the levels of TNF-α and IL-1β in the model of peritonitis induced by carrageenan. Considering the results obtained in this study, is evident that FAEHc, FHAHc and flavonoids lespedin and tiliroside, chemical markers of this plant, have antinociceptive activity, but this effect cannot be attributed only to the markers, since the effect was lower than that shown by the phases and the crude extract. Also, the antinociception induced by FAEHc possibly involves activation of adenosine and muscarinic receptors as well as the nitric oxide pathway. Furthermore, FAEHc is capable of promoting a reduction of inflammation, and this effect is related to the reduction of leukocyte influx to the site of inflammation that could be attributed to inhibiting of the production of TNF-α and IL-1β